Entry timing and innovation strategy in feature phones - Klingebiel, Ronald; Joseph, John (Strategic Management Journal, 2016)
Research summary : This inductive study examines how firms make decisions about the timing of innovations, focusing on the mobile handset industry during the feature‐phone era. Through qualitative and quantitative data, we reveal how individual technology‐entry decisions are influenced by a portfolio‐level timing preference, and how this preference informs other aspects of innovation strategy, too. Early movers address greater, more uncertain revenue opportunities with broader, less selective innovation portfolios. Conversely, late movers target lower, more certain revenue opportunities with narrower, more selective portfolios. While timing per se seems unrelated to performance, a timing‐strategy alignment is. Future research on the equifinal configurations we propose—broad/nonselective for early movers and narrow/selective for late movers—could thus help resolve the debate about the link between timing and performance. Managerial summary : We study how firms make decisions about the entry of new product features, in this case mobile phone technologies. During development firms weigh the scale and likelihood of features' commercial success. Some firms display a preference for earlier entry, which offers temporary monopoly rewards if uncertainty resolves favorably, while others tend to opt for later entry, which offers greater certainty but lower rewards due to competitive preemption. The innovation portfolios of these companies thus pursue differently structured opportunities, bringing about different strategic approaches. Since early movers aim for big hits to compensate for a higher failure rate, they launch a broader set of features and exert little selective pressure on the development portfolio. By contrast, late movers' lower payoffs reduce their tolerance for failure, making them launch fewer features and emphasize selectiveness; i.e., they invest in learning from the resolution of uncertainty so as to choose features more discriminately. When we examine innovation performance, timing has no significant effect but matching timing with feature breadth does. Copyright © 2015 John Wiley & Sons, Ltd.